Accumulation, Structural Change, and External Balances in a World with Internationally Traded Environmental Assets - Arslan Razmi (University of Massachusetts, Department of Economics, 2013)
Environmental literature has largely neglected macroeconomic considerations, especially open economy ones. This paper develops a small country framework that seeks to address these issues. Medium- and long-run aspects are explored using standard trade and portfolio balance models, modified to incorporate trade in claims on non-renewable resources (environmental assets). In the medium-run, changes in environmental regulations, saving behavior, and other variables affect the current account, investment, and composition of output. In the long-run, both the sectoral intensity of environment use and the structure of the economy are affected, as are the capital stock and the global distribution of claims on resources. JEL Categories:
Keywords: 330